A hypothetical case study in the oil and gas energy sector : the acquisition of Laredo Petroleum, Inc. by Chevron Corporation - Pavliuk, Bogdan (2018)
The collapse in oil prices in the summer of 2014 marked a structural shift in the energy landscape and gave promise to intensified activity in terms of oil and gas consolidation. In light of this environment, the press was often referencing the cash-rich energy giant Chevron Corporation as likely to pursue lucrative acquisition opportunities. Similarly, the poorly diversified upstream company Laredo Petroleum, Inc. was perceived as a probable target for the larger players. In exploring the justifications for a potential Chevron-Laredo deal from the perspective of year-end 2014, the following findings have been obtained. Firstly, there exists sound strategic rationale: Laredo’s Permian Basin assets and core competencies seem like a good fit for Chevron’s operations. Secondly, the depressed oil price climate has opened a “window of opportunity” for Chevron to acquire Laredo “cheaply”: given a base-case oil price scenario of $60 per barrel, Laredo’s standalone value per share is estimated at $14,48, marking a 40% upside potential to the $10,35 market price. Thirdly, given its generous cash pile of $12,8 billion, Chevron has the means to finance the acquisition entirely with cash. Most importantly, however, minimal synergies are expected to be reaped due to the combined entity’s inability to significantly slash costs, with the per-share value estimated at only $0,71. Lastly, the vast uncertainty surrounding future oil prices poses difficulties in estimating a fair value and therefore in establishing an appropriate purchase price. With the risks outweighing the rewards, the final recommendation is for Chevron to not pursue the deal.